Analisis Kinerja Keuangan Perusahaan Daerah Air Minum Pada Masa Pandemi Covid-19 - Chamalinda, Khy’sh Nusri Leapatra; Faisol, Imam Agus (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2021)
This study aims to analyze financial performance during the Covid-19 pandemic. Assessment of the performance of the financial aspect is measured using three leading indicators, namely Profitability, Liquidity, and Solvency. The profitability ratio consists of the return on equity and the operating ratio, while the liquidity ratio consists of the cash and effectiveness ratio. The data type used is secondary data in the form of financial reports during the Covid-19 Pandemic, namely April, May and June 2020. The data analysis technique uses Common Size analysis. Namely, researchers measure financial statements based on Profitability, Liquidity, and Solvency Ratios, then interpret the calculation results based on the Minister of Public Works Regulation Number 18 of 2007. The study results explain that the PDAM's financial performance in the first three months of the Covid-19 pandemic explained the different conditions in each indicator. The Profitability Ratio in the ROE aspect explains that the company's ability to generate profits using equity has not been maximized. The same thing happened to the operating ratio, which explained that operating expenses' efficiency and control strategy in April was not optimal. The liquidity ratio in the cash ratio indicator is in the excellent category. The billing effectiveness ratio for April and June is in the excellent category. The solvency ratio explains that the three months of the Covid-19 pandemic are in the excellent category.